ALIH KODE DAN CAMPUR KODE BAHASA MAKASSAR KE BAHASA BUGIS DI PELELANGAN IKAN PA’JUKUKANG KABUPATEN BANTAENG - Purwanti, Nita; Asia M; Andi Agussalim AJ (Journal of Applied Linguistics and Literature, 2024)
The main problem in this research is the form of code switching and code mixing between sellers and buyers at the Pa'jukukang fish auction, Bantaeng district. This research aims to describe the forms of code switching and code mixing from Makassar language to Bugis language of sellers and buyers at the Pa'jukukang fish auction, Bantaeng district. This type of research is a qualitative approach with a descriptive qualitative research design. The subjects in this research were sellers and buyers at the Pa'jukukang fish auction, Bantaeng district. The data in this research is in the form of oral data in the form of words, clauses and sentences containing code switching and code mixing from Makassar language to Bugis language sourced from sources, namely sellers and buyers at the Pa'jukukang fish auction, Bantaeng district, which was taken while the conversation process was in progress. Data collection was carried out using recording, listening and note-taking techniques. The results of this research show that there are three forms of code switching at the Bantaeng district fish auction, namely inter-sentence consisting of three data, intra-sentence consisting of three data, and code switching in tags consisting of three data. There are two forms of code mixing, namely the insertion of elements in the form of words consisting of three data and the insertion of elements in the form of phrases consisting of three data.